2020
DOI: 10.1038/s41419-020-02860-9
|View full text |Cite
|
Sign up to set email alerts
|

Yap haploinsufficiency leads to Müller cell dysfunction and late-onset cone dystrophy

Abstract: Hippo signalling regulates eye growth during embryogenesis through its effectors YAP and TAZ. Taking advantage of a Yap heterozygous mouse line, we here sought to examine its function in adult neural retina, where YAP expression is restricted to Müller glia. We first discovered an unexpected temporal dynamic of gene compensation. At postnatal stages, Taz upregulation occurs, leading to a gain of function-like phenotype characterised by EGFR signalling potentiation and delayed cell-cycle exit of retinal progeni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…GS levels in Müller cells were significantly decreased from two months onwards in Yap cKO retinas compared to control ones (Figure 6). Consistently with previous data we published 9 , this was followed in older animals by the downregulation of two other proteins involved in glutamate recycling, namely the inwardly rectifying potassium channel (Kir4.1) 7 and the water channel Aquaporin-4 (AQP4) 28,29 (Figure 6). Of note, although Kir4.1 was downregulated in Müller cell processes, its expression was increased at their endfeet within the ganglion cell layer.…”
Section: Glutamate Recycling Is Impaired In Aged Yap Cko Retinassupporting
confidence: 91%
See 2 more Smart Citations
“…GS levels in Müller cells were significantly decreased from two months onwards in Yap cKO retinas compared to control ones (Figure 6). Consistently with previous data we published 9 , this was followed in older animals by the downregulation of two other proteins involved in glutamate recycling, namely the inwardly rectifying potassium channel (Kir4.1) 7 and the water channel Aquaporin-4 (AQP4) 28,29 (Figure 6). Of note, although Kir4.1 was downregulated in Müller cell processes, its expression was increased at their endfeet within the ganglion cell layer.…”
Section: Glutamate Recycling Is Impaired In Aged Yap Cko Retinassupporting
confidence: 91%
“…YAP is now recognized as a crucial mediator of eye development, homeostasis and disease 9,30,31 . Beside its major functions as a cell-autonomous regulator of key cellular processes (proliferation, differentiation, apoptosis…), YAP also acts at the level of the tissue structure 32 by bridging extracellular matrix changes to the cell through its mechanosensory activity, and by contributing to the establishment and maintenance of cellular junctions within epithelia 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent findings on Yap haploinsufficiency indicate Müller glia dysfunction, late-onset cone degeneration, and reduced cone-mediated visual response [57]. Finally, YAP deficient endothelial cells show damaged retinal vascularisation and obstructive astrocyte network formation and maturation [58].…”
Section: Yap and Actin Cytoskeleton In Eye Development And Diseasementioning
confidence: 95%
“…He et al, 2019; Holt et al, 2017; Miesfeld et al, 2015; Raghunathan et al, 2014; Williamson et al, 2014). Recent work indicated that retinas in Yap1 heterozygous mice exhibited altered Müller cell homeostatic function, and causing late‐onset cone degeneration (Masson et al, 2020). Although these data suggest YAP function in Müller cells for the preservation of cone integrity, the specific requirement for YAP in in other components of retina has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%